A Dynamical Systems Perspective to Characterize the El Niño Diversity in Spatiotemporal Patterns - Huang, Yu; Shi, Ming; Fu, Zuntao (Frontiers in Physics, 2022)
El Niño is the long-lasting anomalous warming of sea surface temperature (SST) and surface air temperature (SAT) over tropical Pacific. Each El Niño event has its unique impacts on the overlaying atmosphere, where the warming exhibits diversity in spatiotemporal patterns. It still remains an open question for discriminating the El Niño diversity, since the single area-averaging SST index often fails to distinguish impacts of the event diversity, which is partially due to the nonlinear and non-uniform variations of the warming patterns. Here we introduce the Dynamical Systems Metrics (DSM) to measure instantaneous dimensions and persistence of the SAT warming patterns over the tropical Pacific. Our results show that different SAT warming patterns can be discriminated by their corresponding values of dimension and persistence, then the central Pacific and eastern Pacific El Niño events can be discriminated by DSM. Particularly, through the analyses on El Niño events, we can interpret the physical meaning of DSM parameters applied to the space-time SAT field: instantaneous dimension reflects whether the sub-regions of the SAT field are consistently varying and to what degree the spatial pattern of anomalies is homogeneous; while instantaneous persistence indicates how long an anomalous SAT pattern can be maintained. This work analyzes the spatiotemporal variability of El Niño from a dynamical systems perspective, and DSM may also serve as a useful tool to study extreme events related to SST anomalies.